1998
DOI: 10.1620/tjem.185.209
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Relations between the Lengths of the Metacarpal Bones and Phalanges: Surgical Significance.

Abstract: The mathematical relationship between the lengths of the metacarpals and phalanges is important in hand surgery because of its role in determining the lengthening of the tubular bone size or the length of a prosthesis. The purpose of the present study is to perform the measurements on the hand radiographs, and to determine possible mathematical relations between the lengths of the metacarpals and phalanges. The lengths and widths of metacarpals and phalanges were measured in millimeters on hand roentgenograms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 7 publications
2
27
1
3
Order By: Relevance
“…They revealed that combining scores from several different bones enable a reasonable estimate of potential age in a test application of the model. Aydinlioglu et al (1998) conducted radiographic measurements for metacarpals and phalanges lengths of the hand, and they pointed out that the morphometric relations between the lengths of metacarpals and phalanges may be useful for surgical interventions, such as lengthening and shortening procedures of metacarpals and phalangeas. As a result of our measurements, we found consistent proportions between the metatarsals and phalanges, similar to their studies.…”
Section: Discussionmentioning
confidence: 99%
“…They revealed that combining scores from several different bones enable a reasonable estimate of potential age in a test application of the model. Aydinlioglu et al (1998) conducted radiographic measurements for metacarpals and phalanges lengths of the hand, and they pointed out that the morphometric relations between the lengths of metacarpals and phalanges may be useful for surgical interventions, such as lengthening and shortening procedures of metacarpals and phalangeas. As a result of our measurements, we found consistent proportions between the metatarsals and phalanges, similar to their studies.…”
Section: Discussionmentioning
confidence: 99%
“…In unilateral cases, distraction lengthening continued until the metacarpal was equal in length to the contralateral normal metacarpal. In bilateral cases, the estimated length of metacarpal was calculated using the method of Aydinlioglu et al 12 (First metacarpal=0.67x second metacarpal=0.71x third metacarpal=0.78x fourth metacarpal=0.84x fifth metacarpal). When the proposed length was reached, adequate bony union was confirmed if cortical continuity was present in a total of 3 anteroposterior and lateral radiographs.…”
Section: Methodsmentioning
confidence: 99%
“…Determining the appropriate amount of lengthening of a short bone is challenging in a bilateral involvement. We used a formula presented by Aydinlioglu et al [1] to determine the amount of metacarpal lengthening. This formula indicates the mathematical relations between the lengths of metacarpal bones and phalanges as follows:…”
Section: Techniquementioning
confidence: 99%